Deciphering archaeological palimpsests with bone micro-fragments from the Lower Magdalenian of El Mirón cave (Cantabria, Spain). (18th August 2018) - Geiling, Jeanne Marie; Marín-Arroyo, Ana B.; Straus, Lawrence G.; González Morales, Manuel R.
Abstract: Modern excavation techniques aim accurately to recover extant archaeological data. Usually bone micro-fragments are gathered as a result, however, during archaeological analysis these remains are often set apart as indeterminate bones and generally do not contribute to the interpretation of the deposits. How to decipher archaeological palimpsests using these small bone fragments is the aim of this paper. El Mirón Cave, located in northern Iberia, contains a very rich Cantabrian Lower Magdalenian deposit (17–15 uncal ka BP) with high densities of faunal remains and artefacts. Here, we present zooarchaeological, taphonomic and spatial distribution analyses of macromammal finds, including those small bone fragments, accumulated during a series of intensive and repeated human occupations found in the outer vestibule excavation area. Our results show that a broad spectrum of activities was performed there, including meat, marrow and grease processing and waste abandonment. We propose that bone micro-fragments must be considered when addressing human subsistence reconstructions from animal remains, as they represent the leftovers of the chaîne opératoire of animal carcass exploitation. The archaeological implications of their inclusion are extremely valuable, especially when deciphering palimpsests. A multidisciplinary approach to study these small animal remains provides information that otherwise would be missed. Abstract :